Malnutrition risk and hospital‐acquired falls in older adults: A cross‐sectional, multicenter study. Issue 4 (9th February 2020) - Eglseer, Doris; Hoedl, Manuela; Schoberer, Daniela
Abstract : Aim: To assess the relationship of malnutrition risk and in‐hospital falls in a patient group of older hospitalized patients (65–79 and ≥80 years). Methods: A cross‐sectional, multicenter, point‐prevalence study was conducted in 68 Austrian hospitals with 3702 hospitalized older patients. The relationship between malnutrition risk and falls was analyzed using univariate and multivariate binary logistic regression analyses. Data were analyzed separately for two age groups, patients were aged 65–79 years ( n = 2320) and ≥80 years ( n = 1382). Results: Prevalence of hospital‐acquired falls was 5.2%, and prevalence of risk of malnutrition was 24.3% (Malnutrition Universal Screening Tool) and 16.2% (definition using body mass index and weight loss). The univariate analysis showed significant associations of malnutrition risk and in‐hospital falls for patients aged ≥80 years (odds ratio 2.1; 95% confidence interval 1.2–3.6) but not for patients aged 65–79 years. The multivariate logistic regression analysis did not show significant associations between malnutrition risk and hospital‐acquired falls. Conclusions: The results of this study show that malnutrition risk is a predictor for in‐hospital falls in very old patients (≥80 years). In this patient group, the screening and assessment of nutritional status as well as nutritional interventions for the prevention/treatment of malnutrition risk should be considered as one important factor for successful fall prevention. Studies are necessary to assess the effect of nutritional interventions as part of a multifaceted fall‐prevention program. Geriatr Gerontol Int 2020; 20: 348–353 .